Apollinaire on the edge : modern art, popular culture, and the avant-garde - Bohn, Willard, 1939- (Faux titre, 2010)
The title of the present study refers to the fact that Apollinaire consistently worked at the cutting edge of modern aesthetics. The volume seeks to rehabilitate four experimental genres in particular that have received relatively little attention. The fi.